Korea s new economic strategy in the globalization era /O. Yul Kwon, Sung-Hee Jwa, Kyung-Tae Lee. - O, Yul Kwon
A collection of papers that were presented originally at the Third Biennial Conference of the Australian Centre for Korean Studies held at Griffith University, Brisbane, Australia, 20-21 September 2001"--p. Ack.